2004
DOI: 10.1177/0093854804265175
|View full text |Cite
|
Sign up to set email alerts
|

Adjudicative Competency in a Juvenile Population

Abstract: Differences in adjudicative competency among juveniles who were either awaiting adjudication (n = 70) or members of an age-matched control group (n = 40) were assessed, and their scores were compared with those of an adult sample. Competency was assessed using the MacArthur Competence Assessment Tool-Criminal Adjudication, which contains three scales: Understanding, Reasoning, and Appreciation. Participants in the comparison group did not complete the Appreciation scale and were compared only on the Reasoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…have IQs below 70; American Psychiatric Association (DSM-IV-TR), 2000). In fact, because the average IQ for juvenile offenders is consistently at least one standard deviation below the population average (Burnett, Noblin, & Prosser, 2004;Goldstein, Condie, Kalbeitzer, Osman, & Geier, 2003;Viljoen, Klaver, & Roesch, 2005), even more are probably in the borderline range of intellectual disability (i.e. IQs ranging from 71 to 84; DSM-IV-TR, 2000).…”
Section: Studymentioning
confidence: 99%
“…have IQs below 70; American Psychiatric Association (DSM-IV-TR), 2000). In fact, because the average IQ for juvenile offenders is consistently at least one standard deviation below the population average (Burnett, Noblin, & Prosser, 2004;Goldstein, Condie, Kalbeitzer, Osman, & Geier, 2003;Viljoen, Klaver, & Roesch, 2005), even more are probably in the borderline range of intellectual disability (i.e. IQs ranging from 71 to 84; DSM-IV-TR, 2000).…”
Section: Studymentioning
confidence: 99%
“…While research has indicated that adolescents 15 and under show high rates of deficits in the legal capacities relevant to adjudication (Burnett, Noblin, & Prosser, 2004;Grisso et al, 2003;Peterson-Badali & Abramovitch, 1992;Peterson-Badali & Abramovitch, 1993;Redlich et al, 2003;Savitsky & Karras, 1984), research has not yet examined the possible rates of impairments under these alternative legal standards.…”
Section: Adjudicative Competencementioning
confidence: 99%
“…Research on psychosocial maturity, temperament, and cognition has shown that differences in developmental trajectories and pathways are precursors of antisocial behavior, delinquency, and other problem behaviors (Lahey et al, 2003;Rutter et al, 1998;Steinberg and Cauffman, 1996). Development is not only important in explaining how often and perhaps why children will break the law, but also their behavior in interactions with legal actors (Burnett et al, 2004;Grisso et al, 2004).…”
Section: Introductionmentioning
confidence: 99%